Systematic Literature Review: The Philosophical Foundations of Education and Social Norms in Indonesia - Sari, Ice Linsa; Septemi, Yulia; Yadi, Supri; Helita, Helita; Elesti, Yesmi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This article presents a systematic literature review of the philosophical foundations of education and social norms in Indonesia. The study explores how philosophical thought especially idealism, realism, and Pancasila values—influences the formation of character, ethics, and educational practices within Indonesian society. Drawing from various national and international studies, this review identifies three key themes: (1) the role of philosophical perspectives in shaping educational goals and curriculum; (2) the relationship between local wisdom and social norms; and (3) the importance of moral and cultural values in building a just and harmonious society. The findings reveal that education in Indonesia is deeply rooted in philosophical traditions emphasizing balance between intellectual, moral, and spiritual growth. Furthermore, local cultural values, such as harmony and mutual respect, continue to guide the moral formation of citizens. The study concludes that integrating philosophical principles with social norms is essential to develop an education system aligned with Indonesian identity and the ideals of Pancasila.